Dawn Wake Up Watch / Muhammad Helmi Darwis - Darwis, Muhammad Helmi (2020)
Emperor Crimson Sdn Bhd provide business of selling our first innovation which is called Dawn Wake Up Watch. This product is a wristwatch that have several features such as vibrating alarm, prayer times, Qibla direction and both Gregorian and Hijri calendar. This product also train people to adjust their body clock to wake up easily early in the morning. Dawn Wake Up Watch also functions as regular alarm and compass for people who travel a lot. Besides that, the watch also allows the wearer to play music stored inside the storage. Our target are mostly Muslim customers that always wanted to pray on time ranged from 12 years old to 60 years old, both male and female. Customers could get our product easily throughout Malaysia through online delivery on our official website, retailer, and wholesaler. Our company could enter the competition between several other famous brand because of the unique features that exclusively available in our product. Our product also has advantages over the competitors in term of cost, marketing strategies and product differentiation. Management team includes Chief Executive Officer, Administrative Manager, Financial Manager, Marketing Manager and Operation Engineer.